KEMAMPUAN PENALARAN ANALOGI SISWA DALAM MATERI PERSAMAAN LINEAR SATU VARIABEL DI SMP KELAS VII - Aula, Nurhalimah; Hamdani, Zubaidah; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aims of this research is to describe students' analogy on reasoning ability to solve the problem of linear equation materials of single variable at grade VII SMP Muhammadiyah Simpang Empat. The research method used is descriptive method through surveyÂ  form research. The subjects of this research are 29 students at grade VII D SMP Muhammadiyah Simpang Empat. The result shows that 3 students (10.34%) from 29 students are in the category of analogy on reasoning ability. The number of students who are in moderate analogy reasoning category is 22 students (75,86%) from 29 students. The number of students who are in low analogy reasoning category is 4 students (13,79%) from 29 students. The conclusion shows that students' analogy on reasoning ability to solve the problem of linear equation material of single variable at grade VII D SMP Muhammadiyah Simpang Empat is in moderate analogy reasoning category. Encoding, Inferring, Mapping, and Applying stages can be achieved by all students from each level of ability ie students who have high ability level, students who have medium ability level, and students who have low ability level.Keywords: Analogi reasoning ability, Problem Solving, Linear equation of single variableÂ